Towards an institutional research data policy: Taking a journey at Singapore Management University - DONG, Danping (Institutional Knowledge at Singapore Management University, 2019)
In recent years, there has been growing interest on Research Data Management, not only from the academic community but also from governments, funders, publishers and research institutions. Research data is increasingly recognized as a valuable output arising out of research activities therefore an asset. It is recognized as a critical evidence in supporting and validating published research claims in the light of an imminent ‘reproducibility crisis’ in some scientific disciplines. In this presentation, we will share the experiences and learnings in developing and supporting the implementation of a Research Data Policy at Singapore Management University (SMU) in collaboration with our research office and campus IT. An overview of the national and institutional context for RDM will be covered in the presentation. We will also discuss the findings from a series of faculty interviews conducted to understand their research workflow, data characteristics, current practices, etc. We hope that our experiences and reflections will help other institutions that are considering or planning to adopt an RDM policy.